2018
DOI: 10.1038/s41419-018-1099-3
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin promotes antitumor immunity and PD-1 antibody efficacy against melanoma by regulating intestinal microbiota

Abstract: Diosgenin, a natural steroidal saponin, can exert antitumor effect by regulating immune function and improving intestinal microbiota. The response to anti-PD-1 immunotherapy is associated with intestinal microbiota and effector T cells in tumor microenvironment. We hypothesize that the modulation of diosgenin on intestinal microbiota can facilitate antitumor immunity and the therapeutic efficacy of PD-1 antibody. In melanoma-bearing C57BL/6 mice, we observed that the anti-melanoma effect of diosgenin relied mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…In addition, diosgenin activates tumor cell autophagy and apoptosis by inhibiting the phosphorylation of phosphoinositide 3-kinase, Akt, and the mammalian target of rapamycin, thereby decreasing signaling through this pathway [31]. Furthermore, diosgenin can improve intestinal microbiota, which may increase immune functions to enhance the therapeutic efficacy of the checkpoint protein, PD-1, when treating melanoma [32]. Our results demonstrated that diosgenin induced time-and concentration-dependent inhibition of MCF-7 and Hs578T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diosgenin activates tumor cell autophagy and apoptosis by inhibiting the phosphorylation of phosphoinositide 3-kinase, Akt, and the mammalian target of rapamycin, thereby decreasing signaling through this pathway [31]. Furthermore, diosgenin can improve intestinal microbiota, which may increase immune functions to enhance the therapeutic efficacy of the checkpoint protein, PD-1, when treating melanoma [32]. Our results demonstrated that diosgenin induced time-and concentration-dependent inhibition of MCF-7 and Hs578T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The momentous discovery that certain proteins act as “immune checkpoints” by regulating the T-cell response has spurred efforts to develop treatments to reverse this effect and restore anti-tumour immune responses 138,139 . In normal circumstances proteins including programmed death protein (PD-1), its ligand (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), function to prevent autoimmunity 140,141 .…”
Section: The Genetic Landscape In Hnscc and Its Clinical Implicationsmentioning
confidence: 99%
“…Previous studies have found that 'yam gruel' can increase the content of Bifidobacterium in the intestinal tract, regulate oxidative stress, relieve inflammatory response and reduce fasting blood glucose (FBG) levels in patients with diabetes (Pang et al, 2017). Studies in animal models of cognitive dysfunction have further revealed that the active components of yam regulate the composition of gut microbiota and improve memory dysfunction (Dong et al, 2018;Tohda et al, 2017). A considerable number of studies have shown that gut probiotics affect the regulation of cognitive function due to two-way communication channels between the gut and the brain, referred to as the 'gut-brain axis' (Hamidi et al, 2019;Martin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%